Mechanism of TRPA1 and TRPV4 Participating in Mechanical Hyperalgesia of Rat Experimental Knee Osteoarthritis - Runlin XING; Peimin WANG; Linrui ZHAO; Bo XU; Nongshan ZHANG; Xiaochen LI (Archives of Rheumatology, 2017)
Objectives: This study aims to observe both transient receptor potential ankyrin 1 (TRPA1) and transient receptor potential vanilloid 4 (TRPV4) expressions in synovial tissues of rats with mechanical hyperalgesia induced by experimental knee osteoarthritis (KOA). Patients and methods: Forty-five four-month-old Sprague Dawley male rats, weight ranging from 440 g to 470 g, were randomly allocated into three groups, namely KOA group, KOA-antagonist group, and normal group. Mechanical withdrawal thresholds of five rats from each group were detected one week before modeling, and two, four, six, and eight weeks after modeling, respectively. Synovial and cartilage tissues from diseased knee were collected after sacrificing the rats eight weeks after modeling so to observe pathological morphology at cartilage tissues and to determine protein and gene expressions of TRPA1 and TRPV4 at synovial tissues. Results: Rats with KOA showed obvious mechanical hyperalgesia from two weeks after modeling to the latest follow-up, eight weeks after modeling. The abnormally low level of mechanical withdrawal thresholds can be increased by TRPA1 and TRPV4 ion channel blockers. Conclusion: Up-regulating expressions of TRPA1 and TRPV4 participate in the occurrence mechanism of mechanical hyperalgesia induced by KOA.